2016
DOI: 10.3109/14767058.2016.1151868
|View full text |Cite
|
Sign up to set email alerts
|

Differential effect of mode of conception and infertility treatment on fetal growth and prematurity

Abstract: Objectives To examine perinatal outcomes in pregnancies conceived by different methods: fertile women with spontaneous pregnancies, infertile women who achieved pregnancy without treatment, pregnancies achieved by ovulation induction (OI) and in vitro fertilization or intra-cytoplasmic sperm injection (IVF/ICSI). Methods Retrospective single-center cohort study including 200 fertile and 748 infertile women stratified according to infertility treatment. The outcome measurements were preterm delivery (PTD), smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 30 publications
0
18
1
Order By: Relevance
“…Prior literature has shown that conception via ART is more detrimental that spontaneous conception. 15,16 Adverse effects of ART have been noted mainly in twin gestation studies and triplet studies when comparing chorionicity. 1,2,17 The biological plausibility is likely intrinsic to ART and maternal characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior literature has shown that conception via ART is more detrimental that spontaneous conception. 15,16 Adverse effects of ART have been noted mainly in twin gestation studies and triplet studies when comparing chorionicity. 1,2,17 The biological plausibility is likely intrinsic to ART and maternal characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…15 Other factors that may contribute to this theory include hormonal effects on the uterine lining, manipulation of the sperm and egg, in-vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) procedure itself, variations in the culture medium, length of time in culture, freezing and thawing mechanisms, delayed fertilization, medications used for stimulation, and luteal phase support. 13,15,16,18 The rising number of highorder gestation pregnancies can likely be attributed to mothers bearing children at an older age, widespread use of ART, and increased number of embryos being transferred. 6 Of the limited studies available, most are retrospective reviews with many focusing on twin gestation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, ovulation induction and fresh-embryo transfer are associated with an increased risk of small-for-gestational-age and lower birth weight compared with spontaneous conception. [5][6][7][8] As the use of FET is going to increase in the future, it is important to examine the association between FET and fetal growth. Several studies suggest that FET is associated with a higher birth weight Open access than spontaneous, fresh-embryo transfer and non-ART conceptions, 6 as well as with large-for-gestational-age neonates.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the rates of ICSI pregnancies and major congenital anomalies/chromosomal anomalies/syndromes were significantly higher in the SGA group compared with the AGA group, in accordance with the literature ( 16 , 17 , 18 ). Zhu et al ( 18 ) and Valenzuela-Alcaraz et al ( 19 ) reported an increased incidence of SGA infants in women with a history of infertility with or without infertility treatment, and Valenzuela-Alcaraz et al ( 19 ) also described a preferential association of SGA with treated infertility, either by ovulation induction or ICSI. We were not able to compare the study and control groups with respect to this parameter because the history of infertility was not recorded in our data; thus, we can only say that ICSI is a risk factor for SGA, either by itself or due to the history of infertility, not specified in our study.…”
Section: Discussionmentioning
confidence: 99%